Growth and Jobs in Developing Economies : Trends and Cycles - An, Zidong; Ghazi, Tayeb; Gonzalez Prieto, Nathalie; Ibourk, Aomar (Washington, D.C. : International Monetary Fund, 2017)
This paper investigates the relationship between economic growth and job creation in developing economies with a focus on low and lower middle-income countries along two dimensions: growth patterns and short-run correlations. Analysis on growth patterns shows that regime changes are quite common in both economic growth and employment growth, yet they are not synchronized with each other. Okun's Law-the short-run relationship between output and labor market-holds in half of the countries in our sample and shows considerable cross-country heterogeneity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet